Estado nutricional de adultos de 18 a 50 años del sector Curva de Sun- distrito de Moche. Marzo – Abril 2008 - Alfaro Portal, Carlos Alberto (2009)
The nutritional status of the population of Curva de Sun in march and april 2008 using the anthropometric measurements as benchmarks was evaluated. It was evaluated 99 residents (78 women and 21 men) whose ages were between 18 and 50 years, and who met the inclusion and exclusion criteria. The assessment of nutritional status using anthropometric parameters were analyzed, these were the Body Mass Index (BMI), waist hip ratio, skinfold measurement for determining the percentage of fat and mid-arm circumference to assess the reserves of fat and muscle . The results of this study indicate that 35.4% of the population of Curva de Sun overweight, obesity presents a 11.1% type I and 2% have obesity type II. The prevalence of both overweight and obesity was higher in women than men, with p <0.05. Cases of undernutrition were observed in only 10.1% of a population